The Development of Audio-Based Busy Books to Introduce Sex Education to Children Aged 5-6 Years - Binti Sholikatin; Dwi Nurhayati Adhani; Eka Oktavianingsih (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
This study aimed to develop busy book developed based on audio to introduce sex education to children. Sex education is not only given when children reach their teens. Children should be introduced to sex education from an early age. This is a preventive measure to prevent sexual violence against children. The material contained in the busy book includes gender introduction, self-identity recognition, how to maintain body hygiene, limits on touching children's bodies, and prevention of sexual violence in children. This research is a RD research that adopts the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research produced a product in learning media as teaching materials to introduce sexual education to children aged 5-6 years. Based on the assessment of the learning media experts, the results were 86.25% in the appropriate category, and the material expert assessment got 91% results in the very feasible category. The response assessment of TK M NU students, Darunnajah Kamal, received 96% with a very decent category. Based on this research, it can be concluded that an audio-based busy book is appropriate to use in the application of the introduction of sex education for children aged 5-6 years.